2010
DOI: 10.1016/j.jml.2009.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Attenuating information in spoken communication: For the speaker, or for the addressee?

Abstract: a b s t r a c tSpeakers tend to attenuate information that is predictable or repeated. To what extent is this done automatically and egocentrically, because it is easiest for speakers themselves, and to what extent is it driven by the informational needs of addressees? In 20 triads of naive subjects, speakers told the same Road Runner cartoon story twice to one addressee and once to another addressee, counterbalanced for order (Addressee1/Addressee1/ Addressee2 or Addressee1/Addressee2/Addressee1). Stories ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
168
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(187 citation statements)
references
References 47 publications
(65 reference statements)
13
168
1
Order By: Relevance
“…Secondly, repeated references are often also reduced acoustically (Aylett & Turk, 2004;Bard, et al, 2000;Fowler, 1988;Fowler & Housum, 1987;Lam & Watson, 2010). Repeated references, when taken out of context and presented to a listener, have been found to be less recognisable for the addressee because their pronunciation is less clear in repeated references than in initial references (Bard, et al, 2000;Galati & Brennan, 2010). Lieberman (1963) found similar acoustic reduction for redundant words, which were shorter and perceived as less intelligible when taken out of context.…”
Section: Reduction In Spoken Repeated Referencesmentioning
confidence: 98%
See 1 more Smart Citation
“…Secondly, repeated references are often also reduced acoustically (Aylett & Turk, 2004;Bard, et al, 2000;Fowler, 1988;Fowler & Housum, 1987;Lam & Watson, 2010). Repeated references, when taken out of context and presented to a listener, have been found to be less recognisable for the addressee because their pronunciation is less clear in repeated references than in initial references (Bard, et al, 2000;Galati & Brennan, 2010). Lieberman (1963) found similar acoustic reduction for redundant words, which were shorter and perceived as less intelligible when taken out of context.…”
Section: Reduction In Spoken Repeated Referencesmentioning
confidence: 98%
“…The production of repeated references occurs when people refer to the same object more than once in the conversation. Research has found that in speech, these repeated references are often reduced in at least two ways (Aylett & Turk, 2004;Bard, et al, 2000;Brennan & Clark, 1996;Clark & Wilkes-Gibbs, 1986;Fowler, 1988;Fowler & Housum, 1987;Galati & Brennan, 2010;Lam & Watson, 2010). Firstly, repeated references to the same target object usually contain fewer words than initial references (Clark & Wilkes-Gibbs, 1986;Galati & Brennan, 2010).…”
Section: Reduction In Spoken Repeated Referencesmentioning
confidence: 99%
“…This suggests that speakers reduce repeated references, irrespective of the needs of the listener. Bard et al (2000) suggest that this pattern of results can be explained by assuming a two-component language production model, consisting of a fast component, which depends on the speaker's knowledge, and a slow, optional component drawing inferences about what the listener knows (but see e.g., Galati & Brennan, 2010;Galati & Brennan, 2014 for a different take on this issue).…”
Section: Reduction In Speechmentioning
confidence: 99%
“…Whether the linguistic form that speakers choose for their referring expression can be seen to reflect this cooperative principle has been one of the central issues in studies of dialogue. In the present study, we focused on anaphoric expressions, that is, expressions (e.g., pronouns) that refer back to a recently mentioned constituent and investigated whether the form of these expressions differed when speakers completed a picture story to an addressee and when they completed the same picture story without an addressee being present.The idea that speakers adapt to their addressees' needs and knowledge in their contributions to the on-going dialogue has been termed audience design (e.g., Clark & Murphy, 1982;Galati & Brennan, 2010;Horton & Gerrig, 2002). According to collaborative models of discourse (e.g., Brennan & Clark, 1996;Hanna & Tanenhaus, 2004;Heller, Gorman, & Tanenhaus, 2012;Horton & Gerrig, 2002, 2005Lockridge & Brennan, 2002;Metzing & Brennan, 2003) While some discourse theories assume audience design, others claim that speakers may not necessarily construct their utterances completely with their listeners in mind but might have a more self-centred point of departure and only later adjust to the needs of their listeners (e.g., Horton & Keysar, 1996;Keysar, Barr, & Horton, 1998).…”
mentioning
confidence: 99%